A whisper toward peace: A theoretical analysis of the council for a parliament of the world religions - Bloch, Jon P (Journal for the Scientific Study of Religion, 2008)
The Council for a Parliament of the World Religions has been meeting since 1993 to foster a global religious ethic toward world peace, based on the premise that major world religions share this ethic in common. Roland Robertson's multidimensional model of globalization is utilized to analyze the Parliament's foundational Declaration, and explore why the Parliament's message is not receiving wider attention. Excerpts from anti-Parliament sources are included. Based on this analysis, the Parliament appears to have a limited conception of globalization, and so offers but a partial knowledge claim on how religion can resolve global problems. Seen in this light, it is not surprising that some oppose the Parliament's agenda, feel alienated by it, or-given its limitations-are not aware of it.
Keywords: dept.soc

Book Review: The path of the devil: early modern witch hunts. by gary jensen. her hidden children: the rise of wicca and paganism in america. by chas s. clifton. new age and neopagan religions in america. by sarah m. pike. witchcraft and magic: contemporary north america. edited by helen a. berger. voices from the pagan census: a national survey of witches and neo-pagans in the united states. by helen a. berger, evan a. leach, and leigh s. shaffer. researching paganisms (the pagan studies series). edited by jenny balin, douglass ezzy, and graham harvey - Bloch, Jon P. (Journal for the Scientific Study of Religion, 2008)
Keywords: book.review; dept.soc